1980
DOI: 10.1152/ajpheart.1980.239.5.h664
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic NaCl and severe hemorrhagic shock

Abstract: Intravenous infusions of highly concentrated NaCl (2,400 mosmol/l; infused volume 4 ml/kg; equivalent to 10% of shed blood), given to lightly anesthetized dogs in severe hemorrhagic shock, rapidly restore blood pressure and acid base equilibrium toward normality. No appreciable plasma volume expansion occurs for at least 12 h, indicating that fluid shift into the vascular bed plays no essential role in this response. Initial effects wee sustained indefinitely; long term survival was 100%, compared to 0% for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
0
38

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(216 citation statements)
references
References 0 publications
6
167
0
38
Order By: Relevance
“…Estes dados confirmam os obtidos por Velasco et al (1980) e Kramer (1986), que descreveram que a administração de solução NaCl 7,5% aumentou a PAM, o DC e corrigiu os distúrbios metabólicos, por período superior a seis horas.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Estes dados confirmam os obtidos por Velasco et al (1980) e Kramer (1986), que descreveram que a administração de solução NaCl 7,5% aumentou a PAM, o DC e corrigiu os distúrbios metabólicos, por período superior a seis horas.…”
Section: Resultsunclassified
“…A constatação de que o emprego de pequeno volume de solução hipertônica de cloreto de sódio (NaCl 7,5%) promovia restabelecimento imediato e definitivo dos parâmetros hemodinâmicos de cães submetidos a choque hemorrágico grave fez surgir um novo conceito na terapia do choque. A administração de solução hipertônica aumentou a pressão arterial média (PAM), o débito cardíaco (DC) e corrigiu os distúrbios metabólicos, por período superior a seis horas (Velasco et al,1980;Kramer, 1986). A taxa de sobrevida foi de 100% nos animais tratados com NaCl 7,5% enquanto os animais que receberam somente NaCl 0,9% morreram nas primeiras 6,5 horas após a indução da hipovolemia.…”
Section: Introductionunclassified
“…In the controlled hemorrhage studies, investigators commonly administered equal volumes of hypertonic and isotonic saline. [2][3][4][5][6][7] The hypertonic saline-treated animals therefore received significantly greater sodium loads as compared with the isotonic saline-treated animals. The relevance of this becomes apparent when one considers the mechanisms by which HTS is thought to restore hemodynamics: 1) by inducing an osmotic fluid shift from the intracellular to the extracellular space, resulting in intravascular expansion, 2) by decreasing total peripheral resistance, and 3) by increasing myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies of acute hemorrhagic hypotension have demonstrated that smallvolume infusions of HTS and HSD are more effec-tive in increasing BP, increasing cardiac output, and providing volume expansion as compared with conventional isotonic crystalloids. [2][3][4][5][6][7][8][9][10] Based on these studies, several authors have advocated the out-of-hospital administration of hypertonic crystalloids for acute hemorrhagic shock. However, not all of the hypertonic saline studies have demonstrated improvement in outcome from resuscitation of acute hemorrhage.…”
mentioning
confidence: 99%
“…The use of small-volume hypertonic solutions for ressuscitation has proved to be an interesting alternative in experimental models of hemorrhagic shock 6 . Pioneer studies conducted in Brazil in the eighties have revealed that the infusion of small volumes of 7.5% NaCl solution produces rapid restoration of hemodynamic parameters and thus less demand for blood transfusions 7 . Subsequently, it was demonstrated that the addition of a hypertonic solution could increase and prolong the beneficial effects of a hyperoncotic solution 8 .…”
Section: Introductionmentioning
confidence: 99%